2017
DOI: 10.1016/j.genhosppsych.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle interventions for weight loss among overweight and obese adults with serious mental illness: A systematic review and meta-analysis

Abstract: Objective To conduct a systematic review and meta-analysis to estimate effects of lifestyle intervention participation on weight reduction among overweight and obese adults with serious mental illness. Method We systematically searched electronic databases for randomized controlled trials comparing lifestyle interventions with other interventions or usual care controls in overweight and obese adults with serious mental illness, including schizophrenia spectrum or mood disorders. Included studies reported cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 56 publications
2
104
0
3
Order By: Relevance
“…24 Scheduled sessions went ahead but, when support contacts were attempted, they were not always successful (14). During the trial period, we reached a small fraction of those who were potentially eligible in the study areas (15).…”
Section: Results Of the Process Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Scheduled sessions went ahead but, when support contacts were attempted, they were not always successful (14). During the trial period, we reached a small fraction of those who were potentially eligible in the study areas (15).…”
Section: Results Of the Process Evaluationmentioning
confidence: 99%
“…Over the course of the STEPWISE trial, several other long-term studies examining the effect of lifestyle interventions were published and are included in the most recent systematic review. 15 Six studies reported that interventions lasting for more than 1 year showed a more consistent weight reduction (SMD = −0.24, 95% CI −0.36 to −0.12), although only two of the six studies recorded a statistically significant weight loss, both of which included substantial numbers of people with other severe mental illnesses.…”
Section: Chapter 7 Discussionmentioning
confidence: 99%
“…In contrast to the paucity of trials in patients with PD, we have identified 10 systematic reviews investigating interventions to improve the cardiovascular health or cardiovascular risk profile of people with SMI [38][39][40][41][42][43][44][45][46][47]. Moreover, most of these reviews did not include people with PD.…”
Section: Discussionmentioning
confidence: 99%
“…This approach could include focusing on increasing levels of physical activity and to achieving and maintaining a healthy weight. Although these interventions are not yet widespread, some have been developed for use with people with psychosis 94. Health care–level interventions are also limited, with many aiming at increasing access to care or to health-screening services.…”
Section: Multilevel Factors Influencing Access To Specialized Carementioning
confidence: 99%